Inositol Polyphosphate‐5‐Phosphatase in the Development of Head and Neck Squamous Cell Carcinoma. (23rd August 2013) - Patel, Alpen B.; Landry, April M.; Sekulic, Aleksandar; Hayden, Richard E.
Abstract : Objectives: 1) Evaluate the expression patterns of inositol polyphosphate‐5‐phosphatase (INPP5A), a negative regulator of inositol signaling, in the development and progression of head and neck mucosal squamous cell carcinoma (SCCA). 2) Compare and contrast previously reported reduction in INPP5A protein levels seen in the progression of cutaneous SCCA with that of mucosal head and neck SCCA. Methods: We analyzed a series of mucosal oropharyngeal lesions ranging from normal mucosa to invasive SCCA in order to identify genetic changes associated with SCCA development. Immunohistochemistry (IHC) was performed to evaluate INPP5A protein levels in primary SCCA tumors. Formalin fixed, paraffin embedded tissues were sectioned and incubated with anti‐INPP5A antibody and the INPP5A protein expression levels quantified. Results: Deletions of a region on chromosome 10q harboring the INPP5A gene in cutaneous SCCA have previously been reported. INPP5A protein levels have been found to be frequently reduced in primary cutaneous SCCA tissues and demonstrate an early event in the progression of SCCA with further reduction in metastatic disease. A direct comparison of INPP5A protein levels in oropharyngeal mucosal head and neck SCCA has been made with data previously seen with cutaneous SCCA. Conclusions: Previous studies have shown that INPP5A loss is seen with cutaneous SCCA proliferation. This study provides a comparison of INPP5A protein levels in progressive mucosal oropharyngeal SCCA with that seen in cutaneous SCCA.